2015
DOI: 10.1002/lary.25267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resection depth of early glottic cancer on vocal outcome: An optimized finite element simulation

Abstract: Objectives/Hypothesis To test the hypothesis that subligamental cordectomy produces superior acoustic outcome than subepithelial cordectomy for early (T1-2) glottic cancer that requires complete removal of the superficial lamina propria but does not involve the vocal ligament. Study Design Computer simulation Methods A computational tool for vocal fold surgical planning and simulation (the National Center for Voice and Speech Phonosurgery Optimizer-Simulator) was used to evaluate the acoustic output of alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
2
14
1
Order By: Relevance
“…It has been shown that the postoperative voice outcome in limited resections such as subepithelial and subligamental resections (type I‐II according to the European Laryngological Society [ELS] classification) is normal or near to normal and that voice outcome for TLM and RT in these lesions is comparable . However, the postoperative voice is generally poorer in more extended resections (type III‐IV) than in superficial resections (type I‐II) . This is consistent with greater glottal insufficiency due to tissue loss .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It has been shown that the postoperative voice outcome in limited resections such as subepithelial and subligamental resections (type I‐II according to the European Laryngological Society [ELS] classification) is normal or near to normal and that voice outcome for TLM and RT in these lesions is comparable . However, the postoperative voice is generally poorer in more extended resections (type III‐IV) than in superficial resections (type I‐II) . This is consistent with greater glottal insufficiency due to tissue loss .…”
Section: Introductionmentioning
confidence: 88%
“…However, the postoperative voice is generally poorer in more extended resections (type III‐IV) than in superficial resections (type I‐II) . This is consistent with greater glottal insufficiency due to tissue loss . Moreover, when the tumor extends to the anterior commissure (AC), poorer voice outcome is seen, regardless of the treatment modality .…”
Section: Introductionmentioning
confidence: 90%
“…For humans who do not vocalize out of the context of speech, however, the vocal ligament may become superfluous. Surgeons have found that removal of the ligament (known as a cordectomy) may not have a profound effect on conversational speech (Hillel et al, 2013; Mau et al, 2015). Caution should be used, however, in applying this perspective to current surgical management of the vocal ligament.…”
Section: Methodsmentioning
confidence: 99%
“…A computer model published by Mau in 2015 provides theoretical support for this finding although the authors state that further clinical data are required to support this conclusion [105•].…”
Section: Functional Outcomes Of Tlmmentioning
confidence: 99%